Responsiveness to Mannitol in Asthmatic Subjects with Exercise- and Hyperventilation-induced Asthma - BRANNAN, JOHN D.; KOSKELA, HEIKKI; ANDERSON, SANDRA D.; CHEW, NORA (American journal of respiratory and critical care medicine, 1998)
We investigated airway responsiveness to mannitol, a new hyperosmolar challenge, in persons hyperresponsive to airway drying. We studied 36 asthmatic subjects, 18 to 40 yr of age, responsive to exercise (n = 23) and eucapnic hyperventilation (n = 28) defined by a 10% fall in FEV1. Fifteen subjects performed both challenges. All subjects performed a challenge with dry powder mannitol, encapsulated and delivered via a Dinkihaler until a 15% decrease in FEV1 was documented or a cumulative dose of 635 mg was delivered. All subjects responsive to eucapnic hyperventilation and all but one subject responsive to exercise were responsive to mannitol. Sixty-nine percent of subjects had a positive response to mannitol after less than 155 mg (6 capsules) and 94% less than 320 mg (10 capsules). The provoking dose of mannitol required to cause a 15% fall in FEV1 (PD15) was related to the severity of the response to exercise (Pearson's correlation coefficient [rp] = 0.68, p < 0.01) and eucapnic hyperventilation (rp = 0.68, p < 0.01) in subjects who were not taking inhaled corticosteroids. The mean (+/- SD) maximum percent fall in FEV1 after mannitol was 24.4 +/- 6.2% and recovery to bronchodilator occurred within 10 min in most subjects. The mannitol test is simple, inexpensive, faster to perform than hyperpnea with dry air and could become an office-based test. Further studies are now required to determine the sensitivity of mannitol to identify exercise-induced asthma in a random population.